(untitled) (International Journal of Design (INJUDES), 2023)
The research aimed at describing the marketing design to be applied to the CV.X and studying the problems as a foothold of innovation for marketing design. Marketing Division CV. X as a business engaged in the business of decoration. The research used the qualitative method with a literature research approach. In this study, the use of data sources in the form of primary and secondary data was obtained from the results of reviewing the previous research related to the design of various products’ marketing systems using documentation collection methods. A company’s ability to adjust to the times will reduce marketing techniques in the form of brochures because it is rather difficult to influence consumers effectively and efficiently regarding information and purchasing prospects. We gave a study of marketing design based on industrial revolution 4.0 to make the marketing mix wider. It can be concluded that the efforts that are beneficial to the marketing division can be a recommendation for concepts that will be applied in current marketing and informatively explain the goods offered because, with the support of the marketing division, the process of selling goods will be more effective.